Qur’anic Models for Social Welfare Policy: Insights from Prophet Yusuf and Zulkarnain in Addressing Indonesian Social Justice Challenges - Hibatullah, Alif; Niam, Muh. (Jurnal Sosiologi Agama Indonesia (JSAI), 2025)
Indonesia’s diverse society faces persistent challenges from environmental uncertainty and social conflict, which threaten both economic security and social cohesion. Existing welfare initiatives, such as the bantuan sosial (bansos) program and food estate projects, have achieved limited success due to structural weaknesses, inaccurate targeting, and the risk of long-term dependency. These issues point to the need for an ethically grounded and contextually relevant welfare policy framework. This study introduces a normative model of social welfare based on Qur’anic narratives—specifically the stories of Prophet Yusuf and Zulkarnain—interpreted through Paul Spicker’s social welfare theory. Utilizing a qualitative descriptive approach and content analysis of Qur’anic verses, the research identifies core principles aligned with Spicker’s framework: basic needs fulfillment, rights protection, and equitable resource access. This integration of Qur’anic ethics with modern welfare theory offers a novel policy perspective for Indonesia. Key findings show that Prophet Yusuf’s approach to social assistance relied on barter systems to foster independence, complemented by strategies emphasizing job creation, sustainable land use, and active collaboration between government and society. The involvement of social workers as strategic partners strengthens policy implementation and community empowerment. While the conceptual model advances theoretical understanding, further empirical validation in real policy contexts is needed. This research demonstrates that social policies rooted in Qur’anic values and contemporary welfare theory can provide a viable pathway toward a more just and prosperous Indonesian society.